ANALISIS DAMPAK KORUPSI TERHADAP PERTUMBUHAN EKONOMI DAN PERKEMBANGAN HUKUM DI INDONESIA - Luth Fiatunnisa, Maiza; Ameliza Azzahra, Siti; Handayani, Sri (Cahaya Ilmu Bangsa, 2025)
This study aims to analyze the impact of corruption on economic growth and legal development in Indonesia. Widespread corruption in both government and private sectors has hindered efficient resource allocation and reduced investment attractiveness. Additionally, corruption practices have contributed to increasing social and economic inequality. In the legal context, despite the existence of various regulations and anti-corruption agencies such as the Corruption Eradication Commission (KPK), the effectiveness of law enforcement remains limited by political intervention and the weakness of law enforcement agencies' integrity. The study concludes that effective anti-corruption efforts depend on strengthening the legal system, enhancing transparency, and consistent law enforcement. Therefore, achieving sustainable economic growth and better governance requires collaboration between the government, society, and the private sector.